HUBUNGAN ANTARA ADVERSITY QUOTIENT DENGAN KEPUASAN KERJA PADA KARYAWAN PT. BINA INSAN SUKSES MANDIRI - ., Juliana Ningsih (MOTIVASI, 2013)
Abstract.Human resources within an organization requires to be considered, organizations that want to move forward and evolve will think of its employees job satisfaction, and job satisfaction in the can by the employee will inspire employees to perform better, it also becomes a chore at PT. Bina Insan Sukses Mandiri always want to give the best to the employees.This study aims to determine the relationship of adversity quotient with job satisfaction to employee PT. Bina Insan Sukses Mandiri. The subjects were the employees who work in the field as much as 130 samples. Use data collected aqversity quotient scale and job satisfaction. Data analysis technique used statistical analysis product korelation moment with SPSS version 13 for windows. The results of this research shows that there is a positive correlation and a very sigfikan between adversity quotient with employee job satisfaction in the PT Bina Insan Sukses Mandiri with a value of R = 0.097 and p = 0.000